Management Strategies for Legal Compliance and Ethical Enforcement in SMEs - Elpina Elpina (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the economy, particularly in job creation and supporting inclusive economic growth. MSMEs often face challenges in understanding and complying with applicable legal regulations. Legal compliance is crucial not only for maintaining business continuity but also for protecting consumer interests, preventing legal disputes, and building a good reputation. This research aims to explore effective management strategies to ensure legal compliance and ethical business practices in MSME operations, particularly in the context of consumer protection under Law Number 8 of 1999. The method used in this research is a qualitative literature review, drawing data from Google Scholar from 1991 to 2024. The study results indicate that in facing the demands of globalization and increasing competition, MSMEs need to strengthen their management strategies for legal compliance and ethical enforcement, particularly in the context of Law Number 8 of 1999 concerning Consumer Protection. Legal compliance and ethical enforcement in MSME businesses are not merely legal obligations but also a solid foundation for sustainable and responsible business growth. By integrating awareness, integration, collaboration, and innovation into management strategies, MSMEs can enhance consumer protection, build trust and customer loyalty, and improve their business reputation and integrity.